(untitled) (Journal of Applied Oral Science, 2021)
Optimal orthodontic force results in maximum rate of tooth movement without tissue damage. Even though starting orthodontic treatment with a thicker archwire may shorten treatment duration, the evidence on the effect of using 0.018-inch NiTi as the first alignment archwire on pulpal blood flow (PBF) status is still scarce. Objectives: to record PBF changes and pain scores associated with using 0.018-inch NiTi as the first alignment archwire during fixed orthodontic treatment. Methodology: Patients were selected from subjects attending postgraduate orthodontic teaching clinics at Jordan University of Science and Technology. In total, forty healthy patients who exhibited mild lower arch crowding were included. A split-mouth trial design was used. Each patient received two archwire sizes at one time joined in the midline by crimpable hook and applied in the lower arch. Patients were assigned into one of two groups based on archwire sizes used. Group 1: 0.014-inch and 0.018-inch NiTi (Six males, 14 females aged 19.4±1.33 years) and Group 2: 0.016-inch and 0.018-inch NiTi (Seven males, 13 females aged 19.6±1.45 years). The archwire size group was randomly allocated with a 1:1 allocation ratio. A Laser Doppler Flowmeter was used to measure PBF at different time intervals (T0-T5). Pain scores were recorded using a visual analogue scale (VAS). A repeated measures ANOVA and a post-hoc Bonferroni comparison tests were conducted to examine differences at the different time points before and during orthodontic alignment. Results: For all studied archwire sizes, PBF decreased 20 minutes after their placement. Most PBF changes occurred within 24hours and continued to decrease until 72 hours after archwire placement where the maximum reduction was reached. Eventually, normal values were reverted within 1 month. PBF changes were similar between all alignment – groups. Conclusions: Initial orthodontic alignment with 0.018-inch NiTi does not cause irreversible changes to pulpal vasculature or produces higher pain scores.